2008
DOI: 10.1002/pmic.200800215
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of 3,4‐methylenedioxymethamphetamine (MDMA, ecstasy)‐mediated mitochondrial dysfunction in rat liver

Abstract: Despite numerous reports citing the acute hepatotoxicity caused by MDMA (3,4-methylenedioxymethamphetamine, ecstasy), the underlying mechanism of organ damage is poorly understood. We hypothesized that key mitochondrial proteins are oxidatively-modified and inactivated in MDMA-exposed tissues. The aim of this study was to identify and investigate the mechanism of inactivation of oxidatively-modified mitochondrial proteins, prior to the extensive mitochondrial dysfunction and liver damage following MDMA exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
110
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(116 citation statements)
references
References 50 publications
3
110
0
3
Order By: Relevance
“…Consistent with the causal role of increased nitroxidative stress in ER stress , we had detected oxidatively modified ER proteins such as glucose-regulated proteins (e.g., Grp78, Grp75), heat-shock proteins (e.g., Hsp71, Hsp70, Hsp60), and protein disulfide isomerase (PDI) in alcohol-exposed hepatoma cells and rat livers Moon et al, 2006;Suh et al, 2004). Similarly, oxidized chaperone proteins were also observed in 3,4-methylenedioxymethamphetamine (MDMA)-exposed rats (Moon, Upreti, et al, 2008) or mice following ischemia-reperfusion (I/R) injury (Moon, Hood, et al, 2008). Petersen and colleagues also reported that alcohol suppressed the activity of triacylglycerol hydrolase (carboxylesterase 3) via decreased glycosylation, contributing to fat (triglyceride) accumulation in alcohol-treated rodents (Galligan, Fritz, Tipney, et al, 2012).…”
Section: Pathological Mechanisms Of Liver Diseasesmentioning
confidence: 74%
See 1 more Smart Citation
“…Consistent with the causal role of increased nitroxidative stress in ER stress , we had detected oxidatively modified ER proteins such as glucose-regulated proteins (e.g., Grp78, Grp75), heat-shock proteins (e.g., Hsp71, Hsp70, Hsp60), and protein disulfide isomerase (PDI) in alcohol-exposed hepatoma cells and rat livers Moon et al, 2006;Suh et al, 2004). Similarly, oxidized chaperone proteins were also observed in 3,4-methylenedioxymethamphetamine (MDMA)-exposed rats (Moon, Upreti, et al, 2008) or mice following ischemia-reperfusion (I/R) injury (Moon, Hood, et al, 2008). Petersen and colleagues also reported that alcohol suppressed the activity of triacylglycerol hydrolase (carboxylesterase 3) via decreased glycosylation, contributing to fat (triglyceride) accumulation in alcohol-treated rodents (Galligan, Fritz, Tipney, et al, 2012).…”
Section: Pathological Mechanisms Of Liver Diseasesmentioning
confidence: 74%
“…In addition, alcohol-mediated redox change with decreased NAD + levels can interfere with the activities of various NAD + -dependent dehydrogenases in the mitochondria, leading to mitochondrial dysfunction (Cederbaum, 2012b;Lieber, 1997). In fact, mitochondrial dysfunction can be observed in experimental rodents exposed to alcohol (Moon et al, 2006), MDMA (Moon, Upreti, et al, 2008), and acetaminophen (APAP) Abdelmegeed et al, 2010). Impaired mitochondrial function were also reported in pathological conditions such as obesity, diabetes (Dey & Swaminathan, 2010;Paradies, Paradies, Ruggiero, & Petrosillo, 2014), and I/R injury (Moon, Hood, et al, 2008) as well as in patients who consumed alcohol (Addolorato et al, 1998;Fromenty et al, 1995;Witschi, Mossi, Meyer, Junker, & Lauterburg, 1994) and NAFLD/NASH patients (Caldwell et al, 1999;Kojima et al, 2007;Sanyal et al, 2001).…”
Section: Pathological Mechanisms Of Liver Diseasesmentioning
confidence: 97%
“…In the present study, we did not measure plasma levels of MDMA after challenge doses of the drug in repetitively treated animals. However, other studies have reported nonlinear pharmacokinetics of MDMA (de la Torre et al, 2000;Mueller et al, 2008;Baumann et al, 2009) and suppressed liver function after repeated MDMA administration (Beitia et al, 2000;Moon et al, 2008;Cerretani et al, 2011). In combination after several days of repeated MDMA administration, these effects might result in elevated circulating MDMA levels after challenge drug injection and subsequent enhancement of neurochemical and electrophysiological effects.…”
Section: Discussionmentioning
confidence: 98%
“…Mitochondria may also be important targets for MDMA hepatotoxicity [116,124,125]. Methamphetamine or MDMA administration caused a rapid and transient decrease in cytochrome oxidase (or mitochondrial complex IV) staining in dopamine-rich regions, such as the striatum, nucleus accumbens and substantia nigra of rats [116], suggesting that increased extracellular dopamine levels may contribute to the inhibition of metabolic function, through ROS or quinones derived from dopamine metabolism.…”
Section: Mitochondrial Dysfunction Induced By Amphetaminesmentioning
confidence: 99%
“…In these cells, MDMA caused mitochondrial impairment and induction of the mitochondrial permeability transition, accompanied by mitochondrial depolarization and depletion of ATP, through uncoupling of oxidative phosphorylation [125]. In the liver, MDMA may cause the oxidative inactivation of key mitochondrial enzymes involved in energy supply, fat metabolism, antioxidant defense, and chaperone activities, such as mitochondrial aldehyde dehydrogenase, 3-ketoacylCoA thiolases, and ATP synthase, which most likely contribute to mitochondrial dysfunction and subsequent liver damage in MDMA-exposed animals [124]. It is possible that MDMA quinone metabolites contribute to inhibition of mitochondrial function by directly interacting with mitochondrial proteins, such as cytochrome c, which can react with quinone electrophiles forming selective adduct "electrophile binding motifs" within the protein [127].…”
Section: Mitochondrial Dysfunction Induced By Amphetaminesmentioning
confidence: 99%